Evolving Decision Rules with Geometric Semantic Genetic Programming - Rasteiro, Diogo Miguel Galveia De Oliveira (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science